The relationship between musical and mathematical abilities to academic performance of fourth year gifted learners in selected secondary school - Javellana, Gerald John T. (2007)
The relationship between musical and mathematical ability to academic performance of fourth year gifted learners in a selected secondary school was assessed in this study. It looked at the Math and Music grades of the students to determine any relevance between these two variables. MIDAS multiple intelligence test and Gordon's Advanced Measures of Music Audiation were employed. The study found a low to moderate correlation between mathematical and musical abilities of the students. The research would thus enable educators to further enhance their Math and Music Programs especially for the gifted.